Physiological responses to shuttle repeated-sprint running - Buchheit, M.; Bishop, D.; Haydar, B.; Nakamura, F. Y.; Ahmaidi, S. (International Journal of Sports Medicine, 2010)
This study investigated the influence of 180° changes of direction during a repeated-sprint running test on performance, cardiorespiratory variables, muscle deoxygenation and post-exercise blood lactate ([La]b) levels. Thirteen team-sport athletes (22±3 yr) performed 6 repeated maximal sprints with (RSS, 6×[2×12.5 m]) or without (RS, 6×25 m) changes of direction. Best and mean running time, percentage speed decrement (%Dec), pulmonary oxygen uptake (VO2), vastus lateralis deoxygenation (Hbdiff) and [La]b were calculated for each condition. Best and mean times for both protocols were largely correlated (r=0.63 and r=0.78, respectively), and were `almost certainly' higher for RSS compared with RS (e. g., 5.30±0.17 vs. 4.09±0.17 s for mean time, with the qualitative analysis revealing a 100% chance of RSS time being greater than RS). In contrast, %Dec was`possibly' lower for RSS (2.6±1.2 vs. 3.2±1.3%, with a 79% chance of a real difference). Compared with RS,VO2 (40.4±4.2 vs. 38.9±3.8 mL/min.kg, with a 90% chance of a real difference) and [La]b (10.0±1.7 vs. 9.3±2.4 mmol/L, with a 70% chance of a real difference) were`possibly' higher. Conversely, there were no differences in Hbdiff (11.5±3.2 vs. 10.9±3.0 Mikro M. With the comparison rated as`unclear'). To conclude, the present results suggest that the ability to repeat sprints can be considered as a general quality. They also suggest that repeated shuttle sprints might be an effective training practice for eliciting a greater systemic physiological load, but perhaps not a greater loading of the vastus lateral.